Um sistema de autenticação de produtos que emprega a criptografia visual - Cicareli, Rodrigo dos Santos (Universidade Federal de São Carlos, 2020)
In the commercial sphere, attempts at fraud and counterfeiting have caused several problems for manufacturers and the consumer market. In view of this scenario, in order to promote greater reliability and security in commercial transactions, several techniques are being used to verify the authenticity of physical products. Among them, the most used are QR Codes (Quick Response Code), holographic stamps and RFID (Radio Frequency Identification). In this work, a product authentication system that uses the visual encryption developed by Naor and Shamir is proposed. This system uses two computationally generated masks that when overlapped allow visual authentication without the need for any computational processing by the customer. With visual encryption, this authentication system was proposed by Cicareli in submitted work .
A product authentication system that employs visual encryption
Keywords: sistemas; segurança; autenticação; máscaras; criptografia visual; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS